Broadband coupled-line directional couplers with high impedance transformation ratio. Issue 7 (10th February 2017) - Wincza, Krzysztof; Gruszczynski, Slawomir
Abstract : A new class of 3-dB impedance transforming directional couplers has been proposed in which the recently published coupled-line couplers, consisting of coupled-line sections having different electrical lengths, have been utilized. The main advantage of the proposed directional couplers is the possibility of obtaining high impedance transformation ratio, thus the known limiting condition of realizable impedance transformation in 3-dB couplers is overcome. Moreover, the proposed directional couplers feature significantly wider operational bandwidths. The theoretical analysis of the proposed impedance-transforming directional couplers has been shown and is fully supported by the measurements of the manufactured model operating in 0.5–1.5 GHz frequency range.